Low‐dose short‐term hepatitis B immunoglobulin with high genetic barrier antivirals: the ideal post‐transplant hepatitis B virus prophylaxis?. Issue 3 (26th May 2015) - Choudhary, N.S.; Saraf, N.; Saigal, S.; Mohanka, R.; Rastogi, A.; Goja, S.; Menon, P.B.; Soin, A.S.
Abstract Background Low‐dose hepatitis B immunoglobulin (HBIG) and nucleos(t)ides analogs (lamivudine/adefovir) used for the prevention of hepatitis B virus (HBV) recurrence after liver transplantation (LT) are associated with some risk of HBV recurrence and antiviral resistance. Methods The study cohort included 176 patients (at least >12 months follow‐up) with HBV cirrhosis/hepatocellular carcinoma who received secondary prophylaxis with indefinite entecavir/tenofovir after living‐donor LT (LDLT). All patients received 10, 000 IU intravenous HBIG in anhepatic phase followed by 600–1000 IU intramuscularly daily for 7 days, weekly for 3 weeks, and then monthly, to keep antiHBs levels >100 mIU/mL for 1 year. Hepatitis B surface antigen (HBsAg) and HBV DNA were tested every 6 months. Results The study cohort is composed of 157 men and 19 women, mean age 47.9 ± 10.1 years, all HBsAg positive, 35 (19.8%) had HBV DNA >2000 IU/mL before LT. After LT, patients received entecavir (n = 126, 71.5%), tenofovir (n = 20, 11.3%), or a combination of entecavir and tenofovir (n = 30, 17% for 3 months), followed by entecavir alone. During follow‐up of 43 (12–117) months, 2 patients (including 1 with non‐compliance) had HBV recurrence. Conclusion In a large cohort of LDLT recipients for HBV‐related liver disease, use of low‐dose short‐term HBIG with high genetic barrier drugs results in a substantially lower incidence of HBV recurrence, even in high‐risk patients.